Urgensi Hak Cuti Wanita Saat Hamil Berdasarkan Hukum Perburuhan - Aulia, Meidina; Ghufriani, Delina Rinasari; Ladjar, Lidwina Tuto; Sigiro, Talenta Ribka; S, Satino (Media Hukum Indonesia (MHI), 2024)
This study examines the urgency of maternity leave rights for female workers based on labor law in Indonesia. According to Article 27 paragraph 2 of the 1945 Constitution of the Republic of Indonesia and Law Number 13 of 2003 concerning Manpower, the state is obliged to provide decent employment opportunities and protect workers' rights, including maternity leave rights for female workers. Although maternity leave rights are clearly stipulated in the law, many companies in Indonesia still neglect or improperly implement these rights, leading to health risks for mothers and children and causing gender discrimination in the workplace. This study employs normative legal methods with a statutory and case approach to analyze how maternity leave rights are implemented and to identify the common issues faced by female workers concerning these rights. The findings indicate that although most companies have adopted maternity leave policies, violations and non-compliance with regulations persist, leading to health and welfare risks for mothers and infants. The protection of maternity leave rights is an integral part of efforts to achieve gender equality and justice in the workplace. Effective implementation of these rights will not only enhance the welfare of female workers and their children but also positively impact employee productivity and morale, as well as overall company development. This study also presents policy recommendations to improve protection and understanding of maternity leave rights to achieve gender equality and justice in the workplace.